High Real Interest Rates Under Financial Liberalization : Is there a Problem? - Galbis, Vicente (IMF Working Papers; Working Paper ;, 1993)
Concerns were raised beginning in the 1980s about the possible detrimental effects of high positive real interest rates under financial liberalization. Using a sample of 28 countries that underwent financial liberalization since the 1970s, the paper examines the evidence about the emergence of high real interest rates and discusses the possible causes and likely effects. Some remedies--preferably preventive--are considered including macroeconormic stabilization, fiscal consolidation, improvements in prudential regulation and supervision of the financial sector, and introduction of an efficient management of indirect monetary policy instruments.